KOMODIFIKASI “HALAL” PADA KAMPANYE VAKSIN DI INDONESIA - M. Tazri; Arina Himatul Husna (MEDIAKOM : Jurnal Ilmu Komunikasi, 2022)
This study discusses messages in government communications about vaccination campaigns. The object of research is the government's message in the vaccination campaign with the "halal" narrative. This study uses the discourse analysis of the Teun Van Dijk model. Discourse analysis looks at how text, sosial cognition and sosial context in a discourse are raised. Data collection in this study will go through the stages of observation, interviews and documentation. The results of this study reveal that the use of "halal" diction in vaccine campaigns in Indonesia is considered capable of building "public trust" so that public doubts about vaccination can be handled properly. Halal is a benchmark for Muslims in consuming various things, including vaccines. So that the use of "halal" in government campaigns is deemed right on target. However, it cannot be denied that in this case the word "halal" has been commodified, meaning "halal" has changed its function and meaning from its actual function.